The Role Of Cash Planning In Budget Absorption: Perception Testing - Agus Bandiyono; Sekar Mayangsari (Jurnal Akuntansi, 2021)
This research aims to observe how cash planning moderates the factors that influence budget absorption. In addition, to see the effect of the quality of budget planning, knowledge of systems and procedures, and competence of human resources on the performance of budget absorption. This research was conducted at the Head Office of the Ministry of Finance using a sample of 66 executive employees in the finance department with a minimum of 1st-degree education and a minimum of 2 years of work. This study uses quantitative methods and all variables are measured based on an interval scale and data processing is carried out using smart PLS. The results showed that cash planning was not proven as a moderating variable. Other results show that only the quality of budget planning has a significant positive effect on the performance of budget absorption. Meanwhile, the knowledge of the system procedure variable and the HR competency variable has a positive but not significant effect on the performance of budget absorption.